Faktor-faktor yang berpengaruh terhadap tingkat pengungkapan laporan keuangan Pemerintah Daerah Kabupaten/Kota di Provinsi Jawa Tengah Periode 2018-2020 - Putra Setiawan, Ricky Sheldy; Maryono, Maryono (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purpose of this research is to analyze how the influence of Local Government Size (UPD), Local Government Dependence Level (TKPD), and Regional Original Income (PAD) on LKPD Disclosure in districts/cities in Central Java during the 2018-2020 period. The population in this study were all LHP 35 districts/cities in Central Java Province during the period 2018-2020 which were obtained directly from BPK RI. There were a total of 105 samples obtained through the Census Sampling technique or taking the entire population to serve as research samples. This research uses the observation method to analyze information related to the data needed for research needs. Based on the results of the research that has been done, it is found that the size of the Regional Government (UPD) can have a significant positive effect, where the greater the UPD value, the greater the level of LKPD disclosure. Likewise with the Local Government Dependence Level (TKPD) which also has a significant positive effect, where the greater the value of the TKPD, the greater the disclosure of LKPD. However, Regional Original Income (PAD) has a negative and insignificant effect. So that the greater the PAD value, the lower the level of LKPD disclosure will be.